Flexible cyanoethyl cellulose-based nanocomposites with superior energy storage capability. Issue 41 (28th September 2022) - Wu, Lukang; Zhao, Jinhao; Li, Zhicheng; Zhai, Yizan; Zhang, Yiling; Zhen, Qiongxuan; Cheng, Yu; Ding, Xiangping; Li, Peng; Liu, Jinjun; Pan, Zhongbin
Abstract : Novel 2D BNNs/cyanoethyl cellulose composite films exhibit a large  U d  of 23.5 J cm −3  along with a high  η  of 83.6% at 680 MV m −1 . Abstract : Flexible dielectric materials for electrostatic energy storage have shown irreplaceable advantages to apply in power modules and modern electronics. However, traditional polymer-based composite films suffer from energy storage performances, for example, discharged energy density ( U d ) < 15 J cm −3 and efficiency ( η ) < 70%. Herein, new polymer-based composite films, which combine two-dimensional BN nanosheets (2D BNNs) and cyanoethyl cellulose (CRC), are designed and prepared utilizing the solution casting method. The combination of phase-field simulations and the experimental results reveals that the band-gap in 2D BNNs acts as a charge-blocking barrier to hinder charge carrier movement and conductive path formation, resulting in significantly improved breakdown strength. Accordingly, the optimized composite films exhibit a large U d of 23.5 J cm −3 along with a high η value of 83.6% at 680 MV m −1, which is the highest U d reported so far using cellulose-based composite films. The current study provides a new paradigm for the development of high-performance and green natural polymer-based dielectric capacitors.